Chefs, drugs and rock & roll : how food lovers, free spirits, misfits and wanderers created a new American profession - Friedman, Andrew, 1967- (Ecco, an imprint of HarperCollins Publishers, 2018)
"Chefs, Drugs and Rock & Roll transports readers back in time to witness the remarkable evolution of the American restaurant chef in the 1970s and '80s. Taking a rare, coast-to-coast perspective, Andrew Friedman goes inside Chez Panisse and other Bay Area restaurants to show how the politically charged backdrop of Berkeley helped draw new talent to the profession; into the historically underrated community of Los Angeles chefs, inclduing a young Wolfgang Puck and future stars such as Susan Feniger, Mary Sue Milliken, and Nancy Silverton; and into the clash of cultures between established French chefs in New York City and the American game changers behind The Quilted Giraffe, The River Cafe, and other East Coast establishments. We also meet young cooks of the time such as Tom Colicchio and Emeril Lagasse who went on to become household names in their own right. Along the way, the chefs, their struggles, their cliques, and, of course, their restaurants are brought to life in vivid detail. As the '80's unspool, we see the profession evolve as American masters like Thomas Keller rise, and watch the genesis of a "chef nation" as these culinary pioneers crisscross the country to open restaurants and collaborate on special events, and legendary hangouts like Blue Ribbon become social focal points, all as the industry-altering Food Network shimmers on the horizon."--Page [2] of cover.